A instrução primária na província de Goiás no século XIX - Abreu, Sandra Elaine Aires de (2006)
History is constructed/reconstructed from traces preserved through time. The relationship between the historian and the sources is one of the bases upon which historical research is built up since the sources are the historian s basic material essential to the reconstitution of the past. These sources are constructed by the historian and so they are part of the historiographical operation. The historian makes use of the archives where the testimonies of the past are kept and preserved. So it has become a central matter to this work to know what kind of sources there are in the archives of Goiás which make it possible to write the history of the primary school in Goiás in the 19th century. The challenge of this research was to identify and put together a variety of sources about the primary school in Goiás in the 19th century. Brazilian educational historiographical production has experienced a process of renewal and widening of the research field. It has reviewed old themes, rebuilt new objects of study, incorporated new themes and new theoretical bases, assimilated new patterns of research and document critique and problematized the sources, besides the interlocution of history of education with other disciplinary fields. This research is located in this context. After analyzing the existing sources and educational historiographical production in Goiás in the 19th century, the primary public instruction in Goiàs in that period was set up as our object of study. The research aims were to analyze the process of creation and expansion of the elementary schools as well as the establishment of the teaching career and the teaching practice. The period from 1835 to 1893 was delimited for the research. The sources of research used in this study were the reports of the presidents of the Province of Goiás, the reports of the inspectors of instruction, swearing- in terms of teachers, examination terms of teachers and students, class maps of teachers, school exercises and other documents. The primary schools in Go iás in the 19th century were re-designed , the teaching career was constituted and the process of institutionalization of primary instruction was closely related to the extent of the social demand for the acquisition of the abilities of reading, writing, counting and praying